Atividade inseticida de produtos químicos e alternativos sobre insetos-praga da cultura do feijoeiro comum - Pratis, Samara Brandão Queiroz (2016)
The study of ecosystem to be handled and the procedures that are realized which limiting the population pest is a determining factor to success of seed production. This analysis aim evaluate the pest fluctuation of beans crop (Phaseolus vulgaris L.) in two harvest, being submitted to application of chemical and alternative products with insecticide action in differents phenological stages of crop. The experiment was conducted in a randomized block design, with four replications and ten treatments, which were: water, pyroligneous extract, cassava, neem, spiromesifen, imidacloprid + beta-cyflutrin, zeta cypermetrin, thiamethoxam + lambda-cyalotrin, thiamethoxam e teflubenzuron. The entomological estimation were made accounting every living insects, with the aid of magnifying glass (10 times) and a shake cloth (1 m). Regarding the agronomic parameters that were analyzed: number of plants per area, height plant, pod numbers per plant, number of seeds per pod, thousand seeds weight and productivity. Was concluded that both chemical and alternative inseticide products have the potential to influence the populations of insect pests D. speciosa, B. tabaci, P. includens, E. kraemei e Orthoptera spp. in two different bean crop. Although low the population means of E. heros, N. viridula and P. includens, they diverged from the behavior of other species sampled , so why, if presented with rising populations, after receiving treatments spiromesifen, zeta cypermetrin, thiamethoxam + lambda-cyalotrin and teflubenzuron, indicating a possible tolerance to insecticides. Regarding the agronomic analysis showed that the average yields, differ from one another, speculating that there was a phytosanitary control through the use of insecticide products, which indirectly influencing this variable